Defective DNA repair increases susceptibility to senescence through extension of Chk1-mediated G2 checkpoint activation - Johmura, Yoshikazu (Sci Rep, 2016)
Susceptibility to senescence caused by defective DNA repair is a major hallmark of progeroid syndrome patients, but molecular mechanisms of how defective DNA repair predisposes to senescence are largely unknown. We demonstrate here that suppression of DNA repair pathways extends the duration of Chk1-dependent G2 checkpoint activation and sensitizes cells to senescence through enhancement of mitosis skipping. Extension of G2 checkpoint activation by introduction of the TopBP1 activation domain and the nondegradable mutant of Claspin sensitizes cells to senescence. In contrast, a shortening of G2 checkpoint activation by expression of SIRT6 or depletion of OTUB2 reduces susceptibility to senescence. Fibroblasts from progeroid syndromes tested shows a correlation between an extension of G2 checkpoint activation and an increase in the susceptibility to senescence. These results suggest that extension of G2 checkpoint activation caused by defective DNA repair is critical for senescence predisposition in progeroid syndrome patients.